A bibliographic listing of minor fruits grown in the Caribbean. Part one: June 1994. The genus Spondias, tamarind (Tamarindus indica), West Indian cherry (Malpighia glabra) - Instituto Interamericano de Cooperación para la Agricultura (IICA) (IICA, 2020)
46 páginas